2015
DOI: 10.4049/jimmunol.1500375
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immune-like γ/δ T Lymphocytes Share Many Common Features with Their α/β T Cell Counterparts

Abstract: To better apprehend γ/δ T cell biological functions in the periphery, it appears crucial to identify markers highlighting the existence of distinct phenotypic and functional γ/δ T cell subsets. Interestingly, the expression of CD44 and Ly-6C subdivides murine peripheral γ/δ T cells into several subsets, with Ly-6C− CD44hi γ/δ T cells corresponding to the IL-17–producing CD27− γ/δ T cell subset exhibiting innate-like features. By comparing the other subsets to naive and memory CD8+ α/β T cells, in this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 58 publications
(59 reference statements)
5
47
0
Order By: Relevance
“…S6C). Furthermore, in agreement with published reports 45, 46 , we found that control IL-17 producing cells had a significantly higher CD44 MFI than IFNγ producing cells (Fig. S6D).…”
Section: Resultssupporting
confidence: 93%
“…S6C). Furthermore, in agreement with published reports 45, 46 , we found that control IL-17 producing cells had a significantly higher CD44 MFI than IFNγ producing cells (Fig. S6D).…”
Section: Resultssupporting
confidence: 93%
“…int gd27 + cells stimulated for 4 d with coated anti-CD3 and anti-CD28 mAb in the presence of IL-6, IL-23, and TGF-b1 were capable of differentiating into IL-17-producing gd T cells (70). We never observed IL-17 production from gd27 + cells upon stimulation with IL-1b plus IL-23, which was performed for 36 h and in absence of TCR engagement.…”
Section: Cd44mentioning
confidence: 59%
“…We never observed IL-17 production from gd27 + cells upon stimulation with IL-1b plus IL-23, which was performed for 36 h and in absence of TCR engagement. Moreover, the plasticity of gd27 + cells proposed by Lombes et al (70) remains to be observed during in vivo responses.…”
Section: Cd44mentioning
confidence: 89%
“…Because CD44 lo conventional gd T cells exhibit many similarities to naive ab T cells, we predict that they may require a combination of cytokines and tonic TCR signaling for homeostatic maintenance. This supposition is supported by a recent study that found similarities between gd T subsets and naive and memory CD8 + T cells (25). Using CD44 and Ly6C to divide gd T cells into subsets, the investigators found that the CD44 lo cells turn over slowly in the steady-state but convert to CD44 hi cells in a lymphopenic environment, much like naive CD8 + T cells.…”
Section: Discussionmentioning
confidence: 76%